2022
DOI: 10.1111/maq.12741
|View full text |Cite
|
Sign up to set email alerts
|

Society for Medical Anthropology Statement on Supreme Court Dobbs v. Jackson Women's Health Organization Decision

Abstract: This statement summarizes key findings from anthropological and related scholarship on the harmful consequences of inadequate abortion access, leading the Society for Medical Anthropology to register profound concern about the recent Supreme Court decision in Dobbs v. Jackson. After circulation to SMA members for input, a finalized version passed a membership vote by an overwhelming margin. This statement complements one produced by the Council for Anthropology and Reproduction, available here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Dobbs has exacerbated these concerns by creating an environment where survivors who become pregnant as a result of RC will have no recourse to end their pregnancy. The birth of a child with an abusive partner can make it legally more difficult to leave (Barrios et al, 2021; Buchbinder, 2022). In communities where housing choice voucher lists are closed, households may be only able to apply for project-based assistance, putting them at the end of a new waiting list if their family size changes.…”
Section: Post-dobbs Challenges For DV Survivorsmentioning
confidence: 99%
“…Dobbs has exacerbated these concerns by creating an environment where survivors who become pregnant as a result of RC will have no recourse to end their pregnancy. The birth of a child with an abusive partner can make it legally more difficult to leave (Barrios et al, 2021; Buchbinder, 2022). In communities where housing choice voucher lists are closed, households may be only able to apply for project-based assistance, putting them at the end of a new waiting list if their family size changes.…”
Section: Post-dobbs Challenges For DV Survivorsmentioning
confidence: 99%
“…From this perspective, and as discussed further below, politics cannot be reduced to identification with political parties or partisan activity-an observation that challenges the totalizing claims of political parties as if partisan opposition realistically reflected a nation bifurcated by a line between mutually antagonistic social fields As Foblets et al have observed, "the relationship between law and anthropology is often forged in the crucible of political life" (Foblets et al, 2022, 4)-a statement that affirms the dynamism, specificity, and relevance of anthropology's contributions to understanding legal and political crisis. Statements from the Society of Medical Anthropology, the Council on the Anthropology of Reproduction and other anthropological communities immediately followed the Dobbs ruling, providing robust ethnographic and other empirical evidence to contest the majority's many sociocultural representations (Andaya et al, 2022a;Buchbinder et al, 2022;Williamson et al, 2022). I lean on those contributions as context for my own narrower purpose, to examine the court's description of its own social reasoning to ask how their discursive opposition of law and politics works in this case, and what might be its implications for legal and political anthropology.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the implicit racial underpinnings of anti‐abortion politics, many activists see the focus on “pro‐choice,” when it ignores the experiences of people of color, as problematic. Without emphasizing those most affected by abortion restrictions, “pro‐choice” discourse ignores the links of the “pro‐life” movement to white supremacy and is likely to lead to increase number of maternal deaths and suicides as pregnant people struggle with being forced to carry their pregnancies to term (Buchbinder et al., 2022). 11…”
Section: Introductionmentioning
confidence: 99%